Thermodynamics-based mean-value engine model with main and pilot injection sensitivity. (November 2016) - Lee, Byungchan; Jung, Dohoy
This paper presents a thermodynamics-based mean-value engine model that predicts the temperature and pressure at the end of each discrete combustion phase, the peak temperature and pressure, and the indicated mean effective pressure. The model has sensitivities to the engine speed, the main and pilot injection quantities and timings, and the temperature and pressure conditions in the intake and exhaust manifolds. Mathematical relationships are established between the input variables and the output variables through the thermodynamic principles of the modified ideal-gas-limited pressure cycle. Modifications to the ideal-gas cycle include the pilot combustion stage, the effective compression ratio based on the fuel injection timing and start of combustion, the effect of the constant-volume burn ratio on combustion, and the exhaust valve opening timing. The model is also augmented with empirical correlations for the ignition delay, the constant-volume burn ratio, and the heat transfer in order to improve the fidelity of the model. It is validated using test data from a Ford 6.7 l diesel engine. Unlike most data-regression-based mean-value engine models, the model presented in this paper does not sacrifice essential details of the underlying physics while providing a computationally efficient simulation tool.